Effectivity of Scientific Approach Oriented Learning in Heredity toward Senior High School Studentss Scientific Creativity - Nailil Inayah; M Thamrin Hidayat; Mohammad Nur (Universitas Negeri Surabaya, 2020)
The purpose of this research was to investigate the effect of scientific approach oriented learning toward senior high school students scientific creativity. This learning was conducted in XII grade of SMA Muhammadiyah 2 Surabaya by using one-group pretest-posttest design. The methods of data collection were using observation, tests, and questionnaires. Data was analyzed using descriptive analysis quantitatively and qualitatively. The results showed that the learning is effective to enhance scientific creativity students based on N-gain and was significant stated through paired sample t-test. Then implementation of learning got students positive response. Overall, it can be concluded that scientific approach oriented learning was effective to train senior high school students scientific creativity.